An N-terminal domain specifies developmental control by the SMAX1-LIKE family of transcriptional regulators in Arabidopsis thaliana - Sun Hyun Chang; Wesley J. George; David C. Nelson (Proceedings of the National Academy of Sciences, 2025)
SMAX1-LIKE (SMXL) proteins in plants are cellular signaling hubs, many of which are posttranslationally regulated by karrikins from smoke, the plant hormones strigolactones (SLs), and/or cues such as light and nutrients. SMXL proteins control diverse aspects of growth, development, and environmental adaptation in plants through transcriptional corepression and interactions with transcriptional regulator proteins. In flowering plants, the SMXL family comprises four phylogenetic clades with different roles. Functions of the aSMAX1 clade include control of germination and seedling development, while the SMXL78 clade controls shoot architecture. We investigated how SMXL roles are specified in Arabidopsis thaliana. Through promoter-swapping experiments, we found that SMXL7 can partially replicate SMAX1 function, but SMAX1 cannot replace SMXL7 . This implies that the distinct roles of these genes are primarily due to differences in protein sequences rather than expression patterns. To determine which part of SMXL proteins specifies downstream control, we tested a series of protein chimeras and domain deletions of SMAX1 and SMXL7. We found an N-terminal region that is necessary and sufficient to specify control of germination, seedling growth, or axillary branching. We screened 158 transcription factors (TFs) for interactions with SMAX1 and SMXL7 in yeast two-hybrid assays. The N-terminal domain was necessary and/or sufficient for most of the 33 potential protein–protein interactions that were identified for SMAX1. This finding unlocks different ways to engineer plant growth control through cross-wiring SMXL regulatory “input” and developmental “output” domains from different clades and lays a foundation for understanding how functional differences evolved in the SMXL family.